2015
DOI: 10.1128/aac.04869-14
|View full text |Cite
|
Sign up to set email alerts
|

Major Pathways of Polymyxin-Induced Apoptosis in Rat Kidney Proximal Tubular Cells

Abstract: bIdentifying the pathways involved in the apoptotic cell death that is associated with polymyxin-induced nephrotoxicity is crucial for the development of strategies to ameliorate this dose-limiting side effect and for the development of novel safer polymyxins. The primary aim of this study was to identify the major pathways which lead to polymyxin-induced apoptosis in cultured rat kidney proximal tubular cells (NRK-52E). Caspase-3, -8, and -9 were activated by polymyxin B treatment in a concentrationdependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…The majority of the filtered polymyxin molecules undergo extensive tubular reabsorption, leading to the very significant accumulation of polymyxin in tubular cells, which causes renal tubular damage (9,(11)(12)(13). Our recent studies demonstrated that polymyxin-induced nephrotoxicity involves apoptosis in kidney tubular cells, which appears to be partially mediated by the generation of reactive oxygen species (ROS) and caspase activation (14)(15)(16). It has been demonstrated that several antioxidants can attenuate polymyxin-induced nephrotoxicity in animals (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…The majority of the filtered polymyxin molecules undergo extensive tubular reabsorption, leading to the very significant accumulation of polymyxin in tubular cells, which causes renal tubular damage (9,(11)(12)(13). Our recent studies demonstrated that polymyxin-induced nephrotoxicity involves apoptosis in kidney tubular cells, which appears to be partially mediated by the generation of reactive oxygen species (ROS) and caspase activation (14)(15)(16). It has been demonstrated that several antioxidants can attenuate polymyxin-induced nephrotoxicity in animals (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Both, caspase-related and BCL-2 proteins, due to participation in the regulation of apoptosis, may be involved in processes related to drug toxicity. It has been found, among others, that caspases are activated during renal cell injury in response to antibiotics [8,9]. One of most important drugs used for systemic fungal infection treatment is amphotericin B (AmB)a natural macrolide antibiotic produced mainly by actinomycetes of the genus Streptomyces.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical settings, the drug is administered as an anionic prodrug, colistin methanosulfate, which is subsequently hydrolyzed to the cationic colistin [3]. The major toxicities of colistin include nephrotoxicity [4] and neurotoxicity [5]. The use of colistin is often limited by nephrotoxicity, affecting up to 55% of recipients [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%